Yeast cell factories for sustainable whey-to-ethanol valorisation towards a circular economy - Patrícia Carvalho (Green Wave Publishing of Canada, 2021)
Cheese whey is the major by-product of the dairy industry, and its disposal constitutes an environmental concern. The production of cheese whey has been increasing, with 190 million tonnes per year being produced nowadays. Therefore, it is emergent to consider different routes for cheese whey utilization. The great nutritional value of cheese whey turns it into an attractive substrate for biotechnological applications. Currently, cheese whey processing includes a protein fractionating step that originates the permeate, a lactose-reach stream further used for valorisation.  In the last decades, yeast fermentation has brought several advances to the search for biorefinery alternatives. From the plethora of value-added products that can be obtained from cheese whey, ethanol is the most extensively explored since it is the alternative biofuel most used worldwide. Thus, this review focuses on the different strategies for ethanol production from cheese whey using yeasts as promising biological systems, including its integration in lignocellulosic biorefineries. These valorisation routes encompass the improvement of the fermentation process as well as metabolic engineering techniques for the introduction of heterologous pathways, resorting mainly to Kluyveromyces sp. and Saccharomyces cerevisiae strains. The solutions and challenges of the several strategies will be unveiled and explored in this review.